Labour market adjustment in Jamaica - Mullings, Robert (2011)
The central purpose of this thesis is to explore the dimensions of labour market adjustment in Jamaica. The paper adopts a microeconometric approach, relying on new and more detailed Jamaica Labour Force Survey data for the period 1983-2006. Over this period, Jamaica has experienced significant expansion in its external trade which has been characterized by a severe import bias. Also, during this time, Jamaica's agricultural and manufacturing sectors experienced declines in their respective employment shares of 44% and 36% while service sectors expanded. One chapter of the thesis explores the empirical link between expanding trade flows and manufacturing labour market adjustment. The thesis also explores whether and to what extent sectoral labour market adjustment in Jamaica has been accommodated by an accompanying occupational transformation. Central to analyzing the issue of occupational adjustment however, is the careful definition of what constitutes a skill in order to elucidate the role of skill specificity in labour market adjustment. The thesis then investigates the incidence of unemployment in Jamaica in an attempt to identify key factors leading to escape from unemployment within a low skilled, high-unemployment, developing country context.